Anthropometric profile and sweat rate in young soccer players - Luciana Rossi; Camila Ortis Escorel de Azevedo; Vanessa Aparecida de Brito Reis (Universidade Federal de Santa Catarina, 2009)
Soccer is a sport whose worldwide acceptance has been growing year after year, and is one of the most important events in the sports world. A growing number of children and teenagers are engaged in this activity, but studies regarding risk factors such as adiposity and negative impacts such as dehydration and hyperthermia are scarce. The aim of this study was to evaluate the anthropometric profile, sweat rate and risk of dehydration among young soccer players. For anthropometric assessment, weight, height, circumference measures and skinfold thickness were collected and used for the determination of body mass index and percent body fat of each player. For determination of the sweat rate, players were weighed before and after pre-competition training. Analysis of fat percentage (14.4 ± 3.6%) and the sum of skinfolds showed that the players presented an optimal percentage and activity pattern, probably related to their role in the game. Although low (8.8 ± 6.6 mL/min), the sweat rate varied widely among players, wit the observation of a significant reduction (p<0.05) in final weight. The risk of dehydration was low, but the same cannot be stated for the risk of hyperthermia. Further studies involving this population are necessary to establish an adequate hydration strategy, with emphasis on the monitoring of signs of hyperthermia.